Aldehyde group-containing polymer and preparation method thereof

By using furfural derivatives with hydroxyl groups and polymers with acid anhydride groups for esterification, combined with ammonialysis and neutralization reaction, the problems of low aldehyde group content and complex process in the prior art were solved, and polymers with high aldehyde group content and good water-soluble were prepared, achieving the tunability of aldehyde group density and widespread industrial application.

CN119859209AActive Publication Date: 2025-04-22TSINGHUA UNIVERSITY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510157042.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-04-22
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

In the prior art, when synthesizing aldehyde-containing polymers, vinyl monomers such as acrolein have strong asphyxiation and irritation odors and high toxicity, and the aldehyde content is too low, the preparation process is complicated, making it difficult to meet actual production needs.

Method used

Furfural derivatives with hydroxyl groups are used to react with polymers with acid anhydride groups, and the aldehyde group density is increased through esterification reaction, and the aldehyde group content is adjusted through ammonialysis and neutralization reactions to prepare an aldehyde group-containing polymer with good content and water solubility.

Benefits of technology

It realizes the adjustability of aldehyde group density, simple acquisition of raw materials, simple process, controllable cost, small environmental pollution, and high aldehyde group content, and is suitable for a variety of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859209A_ABST
    Figure CN119859209A_ABST
Patent Text Reader

Abstract

The invention relates to an aldehyde group-containing polymer and a preparation method thereof. The aldehyde group-containing polymer provided by the invention comprises a structural unit derived from a reaction of a furfural derivative with hydroxyl and an anhydride group, the aldehyde group density is adjustable, the raw materials are simple to obtain, and high-value utilization of olefin resources is realized. The preparation method of the aldehyde group-containing polymer is simple in process, controllable in cost and small in environmental pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymers, and in particular relates to an aldehyde-containing polymer and a preparation method thereof. Background Art

[0002] As confirmed by many studies, aldehyde groups, as an important type of functional group, are highly reactive and can participate in a variety of chemical reactions even under mild environmental conditions. For example, aldehyde groups can be converted into carboxylic acids through oxidation reactions and form hydroxymethyl groups through reduction reactions; they can also react with alcohols to form acetals or hemiacetals, and can react with amines to form Schiff bases, etc. Therefore, aldehyde compounds have extensive and important applications in many fields such as organic synthesis, biomedicine, agriculture, textile industry, and construction industry.

[0003] However, in the natural environment, aldehyde-containing molecules are rare, and carbonyl compounds mainly exist in the form of ketones, esters, carboxylic acids, etc. More importantly, many common small molecule aldehyde compounds, such as formaldehyde, acetaldehyde, acrolein, crotonaldehyde, etc., have significant volatility, toxicity, irritation, high biological permeability, and even carcinogenicity, and are prone to oxidation and other reactions under natural conditions, leading to deterioration. Such physical and chemical properties have limited the widespread application of aldehyde compounds to a certain extent.

[0004] A possible solution is to use aldehyde-containing polymers to replace small molecule aldehyde substances, thereby effectively overcoming the above-mentioned shortcomings.

[0005] There are currently two conventional methods for synthesizing aldehyde-containing polymers. One method is to prepare aldehyde-containing polymers by self-polymerization of aldehyde-containing vinyl monomers or copolymerization with other vinyl monomers. For example, in non-patent document 1, 4-hydroxybenzaldehyde and methacryloyl chloride were used as raw materials to synthesize a vinyl monomer containing aldehyde groups, p-formylphenyl methacrylate (FPMA), and then FPMA, methyl methacrylate, and poly (ethylene glycol) methacrylate were used as polymerization monomers to synthesize a ternary random copolymer containing aldehyde groups. This material has both biological reactivity and biological inertness.

[0006] In patent document 1, vinyl monomers containing phosphorylcholine hydrophilic groups and vinyl monomers containing aldehyde groups (methacrolein) are polymerized by simple solution free radical polymerization to synthesize phosphorylcholine polymers containing aldehyde groups, and prepare biomimetic adhesion coatings with cell-like outer membrane structures. However, vinyl monomers containing aldehyde groups, such as acrolein, methacrolein and crotonaldehyde, all have strong suffocating irritation smells, are highly toxic, and are difficult to be used in actual production. In addition, due to the difference in the reactivity of aldehyde-containing monomers and other monomers, the aldehyde content of the aldehyde-containing polymer prepared by copolymerization is too low.

[0007] Another method is to prepare aldehyde-containing polymers by aldehyde modification of polymers, such as oxidizing the primary hydroxyl groups on the polymer chain to aldehyde groups. However, the aldehyde-containing polymers obtained by this method have low aldehyde content, low aldehyde density and poor water solubility. A large amount of organic solvents are required during use, which is not in line with modern environmental protection concepts.

[0008] In this regard, some efforts have been made in the prior art. For example, in Non-Patent Document 2, a water-soluble aldehyde-containing polymer is prepared by using a process step of polymerization followed by oxidation. In the first step, a polymer having a vicinal diol structure in the side chain is obtained by a RAFT polymerization method, and in the second step, the vicinal diol is converted into an aldehyde group by an oxidation reaction of sodium periodate, thereby obtaining an aldehyde-containing polymer in which the aldehyde groups are uniformly distributed on the polymer chain.

[0009] Patent Document 2 adopts the process steps of homopolymerization followed by oxidation to prepare a water-soluble polyaldehyde polymer tanning agent. In the first step, linear polyhydroxyacrylate is synthesized by free radical homopolymerization, and in the second step, the primary hydroxyl groups on the polymer chain are oxidized to aldehyde groups as much as possible by precisely controlling the 2,2,6,6-tetramethylpiperidinyl oxide (TEMPO) catalytic oxidation conditions.

[0010] Citations

[0011] Non-patent document 1: Kim et al., Covalently Assembled Bifunctional CopolymerLayers as a Matrix for Immobilization of Oligonucleotides. Bulletin of the Korean Chemical Society, 2012, 33(4):1401;

[0012] Non-patent literature 2: New Aldehyde-Functional Methacrylic Water-Soluble Polymers. Angewandte Chemie International Edition. 2021, 60, 12032;

[0013] Patent document 1: CN 108715644 A;

[0014] Patent document 2: CN 110041451 A. Summary of the invention

[0015] Problem that the invention aims to solve

[0016] The aldehyde-containing vinyl monomers (such as acrolein, methacrolein and crotonaldehyde, etc.) used in the methods of Non-Patent Document 1 and Patent Document 1 all have a strong suffocating irritating odor and are highly toxic, making them difficult to use in actual production. In addition, due to the difference in reactivity between the aldehyde-containing monomers and other monomers, the aldehyde-containing polymer prepared by copolymerization has too low an aldehyde content.

[0017] The methods in Non-Patent Document 2 and Patent Document 2 have complicated processes and require precise control of reaction conditions.

[0018] Therefore, there is still an urgent need to develop aldehyde-containing polymers with high aldehyde content, high aldehyde density, simple preparation process and good water solubility and preparation methods thereof.

[0019] Solutions for solving problems

[0020] In view of the above problems, the present inventors have conducted long-term and in-depth research and found that the above problems can be solved by reacting a furfural derivative having a hydroxyl group with a polymer having an anhydride group.

[0021] Specifically, the present invention solves the problem of the present invention through the following solutions.

[0022] [1] A polymer comprising a structural unit A, a structural unit B and a structural unit C, wherein

[0023] The structural unit A is at least one selected from the structural units represented by the following formulae (1) to (4):

[0024]

[0025] In structures (3) and (4), M + Metal ions or ammonium ions

[0026] The structural unit B is a structural unit derived from an olefin monomer;

[0027] The structural unit C is at least one selected from the structural units represented by the following formula (5) and formula (6):

[0028]

[0029] In structure (6), M + Metal ions or ammonium ions

[0030] [2] The polymer according to [1], wherein the olefin monomer is at least one selected from monoolefins or diolefins having 2 to 20 carbon atoms, styrene and its derivatives, and condensed aromatic olefins;

[0031] Preferably, the olefin monomer is at least one selected from ethylene, propylene, isobutylene, butadiene, isoprene, cyclopentadiene, dicyclopentadiene, styrene and its derivatives, indene, benzofuran, and benzothiophene;

[0032] Preferably, the olefins are derived from at least one of the following raw materials: C4 fraction, C5 fraction, C8 fraction, C9 fraction, ethylene tar, crude gasoline, C4 and above byproduct fractions of coal-to-olefins, coal tar, and coal-to-liquids.

[0033] The C4 fraction is preferably selected from refining C4 and naphtha cracking C4, and the crude gasoline is preferably selected from pre-ether gasoline, catalytic cracking gasoline, catalytic hydrogenation gasoline, and coking gasoline.

[0034] [3] The polymer according to [1], wherein the content of the structural unit A is 5 to 45 mol%, the content of the structural unit B is 30 to 70 mol%, and the content of the structural unit C is 1 to 35 mol%, based on the total molar number of the structural units of the polymer.

[0035] Preferably, based on the total molar number of the structural unit A and the structural unit C, the content of the structural unit C is 1 to 50 mol %, preferably 10 to 45 mol %.

[0036] [4] The polymer according to [1], wherein the aldehyde group content is 0.05 to 3 mmol·g -1 .

[0037] [5] The method for producing a polymer according to any one of [1] to [4], comprising the following steps:

[0038] (1) reacting a precursor polymer with 5-hydroxymethylfurfural, wherein the precursor polymer comprises a structural unit A represented by formula (1) and a structural unit B derived from an olefin monomer;

[0039] (2) Optionally, subjecting the polymer obtained in step (1) to aminolysis and / or neutralization reaction.

[0040] [6] The preparation method according to [5], wherein

[0041] In step (1), an acid anhydride group in the structural unit represented by formula (1) is subjected to an esterification reaction with a hydroxyl group in 5-hydroxymethylfurfural in the presence of a catalyst; the catalyst is preferably an acid or a base, and the base is preferably one or more selected from pyridine, 4-dimethylaminopyridine, triethylamine, and 1,5,7-triazabicyclo[4.4.0]dec-5-ene; the acid is preferably one or more selected from acetic acid, propionic acid, n-butyric acid, succinic acid, p-toluenesulfonic acid, hydrochloric acid, and sulfuric acid;

[0042] In step (1), the molar ratio of 5-hydroxymethylfurfural to the structural unit represented by formula (1) is (0.1-3):1, preferably (1-2):1;

[0043] In step (2), the polymer obtained in step (1) is contacted with ammonia gas to perform the aminolysis reaction and / or the polymer obtained in step (1) is contacted with a metal hydroxide or a metal carbonate to perform the neutralization reaction.

[0044] [7] The preparation method according to [5], wherein

[0045] In step (1), the precursor polymer is dispersed or dissolved in a solvent, and then 5-hydroxymethylfurfural is added thereto to react the precursor polymer with 5-hydroxymethylfurfural;

[0046] Preferably, the solvent is one or more selected from ketone solvents, ester solvents, ether solvents, amide solvents, and sulfoxide solvents.

[0047] [8] The preparation method according to [6], wherein the temperature of the esterification reaction in step (1) is 40 to 150°C and the time of the esterification reaction is 0.1 to 100 hours; the time of the aminolysis reaction in step (2) is 0.1 to 30 minutes, preferably 1 to 10 minutes; and the time of the neutralization reaction in step (2) is 0.1 to 30 minutes, preferably 1 to 10 minutes.

[0048] [9] The preparation method according to [5] further comprises the following steps:

[0049] (1') subjecting the electron accepting monomer and the olefin monomer to self-stabilizing precipitation polymerization to obtain the precursor polymer;

[0050] Wherein, the electron accepting monomer is maleic anhydride;

[0051] Preferably, at least one selected from the group consisting of C4 fraction, C5 fraction, C8 fraction, C9 fraction, ethylene tar, crude gasoline, C4 and above byproduct fractions of coal-to-olefins, coal tar, and coal-to-liquid is used as the raw material of the olefin monomer;

[0052] The C4 fraction is preferably selected from refining C4 and naphtha cracking C4; the crude gasoline is preferably selected from pre-ether gasoline, catalytic cracking gasoline, catalytic hydrogenation gasoline and coking gasoline.

[0053]

[10] Use of the polymer according to any one of [1] to [4] as a paper sizing agent or a wood adhesive.

[0054] Effects of the Invention

[0055] The present invention has the following beneficial effects:

[0056] 1) The aldehyde group density of the aldehyde group-containing polymer of the present invention is adjustable, the raw materials are easy to obtain, and high-value utilization of olefin resources is achieved;

[0057] 2) The preparation method of the aldehyde-containing polymer of the present invention has simple process, controllable cost and little environmental pollution;

[0058] 3) The aldehyde-containing reagent used in the preparation method of the aldehyde-containing polymer of the present invention is the biomass platform compound 5-hydroxymethylfurfural (5-HMF), which is environmentally friendly, broadens the application of 5-HMF, and is conducive to the improvement of the production capacity of 5-HMF. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 is the polymer P obtained in Example 1 c1 Physical photos of

[0060] Figure 2 is the polymer P obtained in Example 1 b1 Infrared spectrum of

[0061] Figure 3 is the polymer P obtained in Example 1 c1 Infrared spectrum of

[0062] Figure 4 is the polymer P obtained in Example 7 b7 The H NMR spectrum ( 1 H-NMR);

[0063] Figure 5 is the polymer P obtained in Example 7 c7 The H NMR spectrum ( 1 H-NMR);

[0064] Figure 6 is the polymer P obtained in Example 10 b10 Physical photos of

[0065] Figure 7 This is a graph showing the change of water contact angle over time measured in the hydrophobicity test; DETAILED DESCRIPTION

[0066] The following is a detailed description of the present invention. The technical features described below are described based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples.

[0067] <Terms and Definitions>

[0068] In this specification, "self-stabilizing precipitation polymerization" refers to a polymerization method in which no emulsifier is used in the polymerization system and the polymerization product is suspended in the reaction medium.

[0069] In this specification, "electron accepting monomer" refers to a monomer having an electron withdrawing group on the carbon-carbon double bond participating in the polymerization reaction.

[0070] In this specification, "electron donating monomer" refers to a monomer having an electron donating group on the carbon-carbon double bond that participates in the polymerization reaction.

[0071] In the present specification, unless otherwise specifically stated, "alkyl group" means a linear, branched or cyclic alkyl group.

[0072] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0073] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0074] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0075] In this specification, the use of "optionally" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0076] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.

[0077] In this specification, the references to "preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0078] <Polymer>

[0079] An object of the present invention is to provide a polymer comprising a structural unit A, a structural unit B and a structural unit C, wherein

[0080] The structural unit A is at least one selected from the structural units represented by the following formulae (1) to (4):

[0081]

[0082] In structures (3) and (4), M + Metal ions or ammonium ions

[0083] The structural unit B is a structural unit derived from an olefin monomer;

[0084] The structural unit C is at least one of the structural units represented by the following formula (5) and formula (6):

[0085]

[0086] In structure (6), M + Metal ions or ammonium ions

[0087] The polymer of the present invention is a polymer containing aldehyde groups. In some embodiments, the aldehyde group content of the polymer of the present invention is 0.05 to 3 mmol·g -1 , preferably 0.1 to 2.5 mmol·g -1 , more preferably 0.15 to 2 mmol·g -1 , for example 0.18 to 1.4 mmol·g -1 , 0.3mmol·g -1 , 0.4mmol·g -1 , 0.5mmol·g -1 , 0.6mmol·g -1 , 0.7mmol·g -1 , 0.8mmol·g -1 , 0.9mmol·g -1 、1.0mmol·g -1 , 1.1mmol·g -1 , 1.2mmol·g -1 , 1.3mmol·g -1 wait.

[0088] In some embodiments, the polymer of the present invention consists of structural unit A, structural unit B, and structural unit C, and thus can be considered a terpolymer.

[0089] Each structural unit in the polymer of the present invention is described in detail below.

[0090] Structural unit A

[0091] The structural unit A is at least one of the structural units having an anhydride group, an amic acid group, an amic acid salt or a carboxylate as shown in the above formula (1) to formula (4). Specifically, the structural unit shown in formula (1) has a maleic anhydride group, the structural unit shown in formula (2) has a maleamic acid group, the structural unit shown in formula (3) has a maleamic acid metal salt or ammonium salt, and the structural unit shown in formula (4) has a maleic acid metal ion salt.

[0092] In some embodiments, structural unit A comprises a structural unit represented by formula (1).

[0093] In some embodiments, the structural unit A comprises at least one of the structural units represented by formula (2) to formula (4). The structural units represented by formula (2) to formula (4) can give the polymer sufficient water solubility. Therefore, in these embodiments, the polymer of the present invention has good water solubility and excellent solubility in water, and can avoid the use of organic solvents in subsequent applications, which is economical, environmentally friendly, green and safe.

[0094] In some embodiments, structural unit A comprises a structural unit represented by formula (2).

[0095] In some embodiments, structural unit A comprises a structural unit represented by formula (3).

[0096] In some embodiments, structural unit A comprises a structural unit represented by formula (4).

[0097] In some embodiments, the content of structural unit A is 5 to 45 mol%, preferably 10 to 30 mol%, based on the total moles of structural units in the polymer.

[0098] In some embodiments, the metal ion represented by M is one or more selected from alkali metal ions and alkaline earth metal ions, preferably one or more selected from lithium ions, sodium ions, potassium ions, calcium ions, and magnesium ions, and more preferably sodium ions.

[0099] Structural unit B

[0100] The structural unit B is a structural unit derived from an olefin monomer. Specifically, the structural unit B is a structural unit formed by a polymerization reaction (eg, a chain polymerization reaction) of the olefin monomer.

[0101] In some embodiments, the olefin monomer is at least one selected from monoolefins or diolefins having 2 to 20 carbon atoms, styrene and its derivatives, and condensed-ring aromatic olefins.

[0102] Preferably, the olefin monomer is at least one selected from ethylene, propylene, isobutylene, butadiene, isoprene, cyclopentadiene, dicyclopentadiene, styrene and its derivatives, indene, benzofuran, and benzothiophene.

[0103] Preferably, the olefins are derived from at least one of the following raw materials: C4 fraction (including refining C4 and naphtha cracking C4), C5 fraction, C8 fraction, C9 fraction, ethylene tar, crude gasoline (crude gasoline is selected from pre-ether gasoline, catalytic cracking gasoline, catalytic hydrogenation gasoline, coking gasoline), coal-to-olefin C4 and above by-product fractions, coal tar, and coal-to-oil.

[0104] In some embodiments, the content of structural unit B is 30 to 70 mol%, preferably 40 to 60 mol%, based on the total moles of structural units in the polymer.

[0105] Structural unit C

[0106] The structural unit C is at least one selected from the structural units containing an aldehyde group represented by formula (5) and formula (6). The metal ion represented by M can be selected from those described above for the structural unit A.

[0107] In some embodiments, the content of the structural unit C is 1 to 35 mol %, preferably 5 to 30 mol %, and more preferably 10 to 25 mol %, based on the total moles of the structural units in the polymer.

[0108] In some embodiments, based on the total moles of the structural unit A and the structural unit C, the content of the structural unit C is 1 to 50 mol %, preferably 10 to 45 mol %.

[0109] Other structural units

[0110] The polymer of the present invention may also contain other structural units, for example, structural units derived from one or more monomers of the vinyl ether monomers and the vinyl ester monomers.

[0111] In some embodiments, based on the total molar number of structural units in the polymer, the content of other structural units is 10 mol % or less, preferably 5 mol % or less, for example 2 to 4 mol %.

[0112] <Polymer Preparation Method>

[0113] An object of the present invention is to provide a method for preparing the polymer of the present invention, which comprises the following steps:

[0114] (1) reacting a precursor polymer with 5-hydroxymethylfurfural, wherein the precursor polymer comprises a structural unit A represented by formula (1) and a structural unit B derived from an olefin monomer;

[0115] (2) Optionally, subjecting the polymer obtained in step (1) to aminolysis reaction and / or neutralization reaction.

[0116] In some embodiments, the preparation method of the present invention further comprises the following steps:

[0117] (1') subjecting an electron accepting monomer and an olefin monomer to self-stabilizing precipitation polymerization to obtain the precursor polymer; wherein the electron accepting monomer is maleic anhydride.

[0118] The various steps of the preparation method of the present invention are described in detail below.

[0119] Step (1')

[0120] Step (1') is a step of preparing a precursor polymer by self-stabilizing precipitation polymerization. Specifically, an electron accepting monomer and an olefin monomer are subjected to self-stabilizing precipitation polymerization to obtain the precursor polymer.

[0121] The self-stabilized precipitation polymerization of the electron acceptor monomer and the olefin monomer can be carried out in a conventional manner, for example, by the methods described in patent documents CN 113563152 A, patent document CN 115926024 A, and patent document CN 117417481A.

[0122] By using maleic anhydride as an electron accepting monomer, the structural unit represented by formula (1) is introduced into the precursor polymer.

[0123] The olefin monomer used in step (1') may be selected from those described above for structural unit B of the polymer of the present invention.

[0124] In some embodiments, at least one of C4 fraction (including refining C4 and naphtha cracking C4), C5 fraction, C8 fraction, C9 fraction, ethylene tar, crude gasoline (crude gasoline is selected from pre-ether gasoline, catalytic cracking gasoline, catalytic hydrogenation gasoline, coking gasoline), coal-to-olefin C4 and above by-product fractions, coal tar, and coal-to-oil is used as the raw material for the olefin monomer.

[0125] Step (1)

[0126] In step (1), a precursor polymer is reacted with 5-hydroxymethylfurfural to convert at least a portion of the structural units represented by formula (1) in the precursor polymer into structural units represented by formula (5).

[0127] In some embodiments, in step (1), an esterification reaction is carried out between the anhydride group in the structural unit represented by formula (1) and the hydroxyl group in 5-hydroxymethylfurfural in the presence of a catalyst.

[0128] In some embodiments, the catalyst is an acid or a base. The base is preferably selected from one or more of pyridine, 4-dimethylaminopyridine, triethylamine, and 1,5,7-triazabicyclo[4.4.0]dec-5-ene; the acid is preferably selected from one or more of acetic acid, propionic acid, n-butyric acid, succinic acid, p-toluenesulfonic acid, hydrochloric acid, and sulfuric acid.

[0129] In some embodiments, the total esterification rate of the structural units represented by formula (1) after the esterification reaction is 1 to 70 mol %, preferably 2 to 55 mol %, and more preferably 10 to 50 mol %.

[0130] Here, the "esterification ratio" refers to the molar ratio of the total amount of the structural units represented by the formula (5) in the polymer after the esterification reaction to the total amount of the structural units represented by the formula (1) in the precursor polymer.

[0131] The esterification rate is affected by many factors, such as the type and dosage of the catalyst, feed ratio, reaction temperature and reaction time.

[0132] In some embodiments, the amount of the catalyst used is 0.1 to 10% relative to the mass of 5-hydroxymethylfurfural.

[0133] In some embodiments, in step (1), the molar ratio of 5-hydroxymethylfurfural to the anhydride group in the structural unit represented by formula (1) is (0.1-3):1, preferably (1-2):1.

[0134] In some embodiments, the temperature of the esterification reaction in step (1) is 40-150°C.

[0135] In some embodiments, the esterification reaction time in step (1) is 1 to 100 hours.

[0136] In a more specific embodiment, in step (1), the precursor polymer is dispersed or dissolved in a solvent, and then 5-hydroxymethylfurfural is added thereto to react the precursor polymer with 5-hydroxymethylfurfural.

[0137] Preferably, the solvent is one or more selected from ketone solvents, ester solvents, ether solvents, amide solvents, and sulfoxide solvents. Among them, ketone solvents include but are not limited to acetone, butanone, cyclohexanone, methyl isobutyl ketone, methyl isopropyl ketone, etc.; ester solvents include but are not limited to ethyl formate, ethyl acetate, butyl acetate, isoamyl acetate, ethyl butyrate, ethyl benzoate, etc.; ether solvents include but are not limited to tetrahydrofuran, dioxane, dimethyl ether, methyl ethyl ether, ethyl ether, ethyl propyl ether, dipropyl ether, dibutyl ether, methyl propyl ether, methyl butyl ether, methyl isobutyl ether, methyl tert-butyl ether, methyl isopentyl ether, methyl tert-amyl ether, methyl cyclopentyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, etc.; amide solvents include but are not limited to dimethylformamide, dimethylacetamide, etc.; sulfoxide solvents are, for example, dimethyl sulfoxide, etc.

[0138] In some embodiments, the mass ratio of the precursor polymer to the solvent is 1:(1-30).

[0139] In some embodiments, the 5-hydroxymethylfurfural used in the present invention is 5-hydroxymethylfurfural of biological origin, that is, 5-hydroxymethylfurfural prepared using biomass as raw material.

[0140] Examples of biomass for producing 5-hydroxymethylfurfural include cellulose, glucose, and fructose (eg, crude fructose, purified fructose, polyfructose, and fructose syrup).

[0141] Step (2)

[0142] Step (2) is an optional step. In step (2), the polymer obtained in step (1) is subjected to an ammonolysis reaction and / or a neutralization reaction. During the ammonolysis reaction, the anhydride group reacts with ammonia (NH3) to form an amic acid group and / or an amic acid ammonium salt group. Through the ammonolysis reaction, the structural unit shown in formula (1) in the polymer is converted into a structural unit shown in formula (2) and / or formula (3). In the neutralization reaction, the carboxyl group (-COOH) and / or the anhydride group reacts with a base to form a carboxylate, and the anhydride group reacts with a base to form an amic acid salt. Through the neutralization reaction, the structural unit shown in formula (1) in the polymer is converted into a structural unit shown in formula (3) and / or formula (4), and the structural unit shown in formula (5) is converted into a structural unit shown in formula (6).

[0143] In step (2), only the aminolysis reaction, only the neutralization reaction, or both the aminolysis and neutralization reactions may be performed. In the embodiment where both reactions are performed, there is no particular restriction on the order of the aminolysis and neutralization reactions.

[0144] In some embodiments, the polymer obtained in step (1) is contacted with ammonia gas to perform an ammonolysis reaction, and a neutralization reaction is optionally performed after the ammonolysis reaction. From the perspective of facilitating the ammonolysis reaction, it is preferred to use high-purity ammonia gas (gas containing ammonia), for example, an ammonia content of 95% by volume or more, preferably 98% by volume or more, more preferably 99% by volume or more, for example 100% by volume.

[0145] In some embodiments, the duration of the aminolysis reaction in step (2) is 0.1 to 30 minutes, preferably 1 to 10 minutes.

[0146] In some embodiments, the polymer obtained in step (1) is contacted with an alkaline aqueous solution to perform a neutralization reaction, and an aminolysis reaction is optionally performed after the neutralization reaction. From the perspective of facilitating the neutralization reaction, the alkali in the alkaline aqueous solution is one or more selected from sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, and potassium bicarbonate. Preferably, the concentration of the alkaline aqueous solution is 0.01 to 5 mol / L, preferably 0.1 to 1.5 mol / L, and more preferably 0.2 to 1.2 mol / L.

[0147] In some embodiments, the temperature of the neutralization reaction is 20-80°C.

[0148] In some embodiments, the neutralization reaction time is 1 to 60 minutes.

[0149] Additional Steps

[0150] In some embodiments, the preparation method of the present invention further comprises a post-treatment step. Specifically, after step (1) or step (2) (if any), the obtained polymer is separated from the reaction system and optionally purified, dried, etc.

[0151] The present invention has no particular limitation on the post-treatment step, and any suitable method known in the art may be used.

[0152] <Purpose>

[0153] It is an object of the present invention to provide the use of the polymers of the present invention as paper sizing agents.

[0154] It is an object of the present invention to provide the use of the polymers according to the invention in wood adhesives.

[0155] Example

[0156] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0157] The description of the raw materials in the following examples is as follows:

[0158] Styrene-maleic anhydride linear copolymer (SMA): Mn = 45000 g·mol -1 , MAH unit content is about 50%. Synthesis method: 10g styrene, 10g maleic anhydride, 0.2g azobisisobutyronitrile, 180g isoamyl acetate are put into a reaction bottle, nitrogen is passed for 15min. After reacting at 70℃ for 6h, centrifuge, wash and dry.

[0159] Isobutylene-maleic anhydride linear copolymer (IB-MA): purchased from Shanghai Adamas Reagent Co., Ltd., CAS No.: 6426-80-2, Part No.: 121947BC

[0160] Propylene-maleic anhydride linear copolymer (PP-MA): Synthesis method: 3g propylene, 10g maleic anhydride, 0.2g azobisisobutyronitrile, and 120g isoamyl acetate were added to a reactor and nitrogen was passed through for 15 minutes. After reacting at 70°C for 6 hours, the mixture was centrifuged, washed, and dried.

[0161] Dephenolized phenol oil-maleic anhydride linear copolymer (DPPO-MA): Synthesis method: 20g dephenolized phenol oil, 10g maleic anhydride, 0.2g azobisisobutyronitrile, 180g isoamyl acetate were put into a reaction bottle, nitrogen was passed for 15min, reacted at 70℃ for 6h, centrifuged, washed and dried.

[0162] C5 fraction-styrene-maleic anhydride linear copolymer (C5-MA): Synthesis method: 5g C5 fraction, 5g styrene, 10g maleic anhydride, 0.2g azobisisobutyronitrile, 180g isoamyl acetate were added to a reaction bottle, nitrogen was passed for 15min, reacted at 70℃ for 6h, centrifuged, washed and dried.

[0163] C9 fraction-styrene-maleic anhydride linear copolymer (C9-MA): Synthesis method: 5g C9 fraction, 5g styrene, 10g maleic anhydride, 0.2g azobisisobutyronitrile, 180g isoamyl acetate were added to a reaction bottle, nitrogen was passed for 15min, reacted at 70℃ for 6h, centrifuged, washed and dried.

[0164] 5-Hydroxymethylfurfural (5-HMF): purchased from Shanghai Aladdin Company, CAS No.: 67-47-0, item No.: H106324-25g

[0165] 4-Dimethylaminopyridine (DMAP): purchased from J&K, CAS No.: 1122-58-3, Part No.: 117147

[0166] Triethylamine (TEA): purchased from J&K, CAS No.: 121-44-8, Part No.: 959833

[0167] Sodium hydroxide (NaOH): purchased from Shanghai Titan Technology Co., Ltd., CAS number: 1310-73-2, item number: 01410952

[0168] Test Method

[0169] Esterification rate:

[0170] The esterification rate was calculated by the nuclear magnetic resonance hydrogen spectrum integral area method, where a is the peak of aldehyde hydrogen, located at 9.5ppm, b is the peak of aromatic hydrogen on the benzene ring, located at 5.8-7.6ppm, and the result of deducting the two double bond hydrogens in the 5-hydroxymethylfurfural structure located at 6.7 and 7.5ppm. The calculation formula is:

[0171]

[0172] Aldehyde content:

[0173] The aldehyde content is calculated by the mass method, w0 is the mass of the polymer precursor, and w1 is the mass of the polymer after the introduction of 5-hydroxymethylfurfural. The calculation formula is:

[0174]

[0175] Example 1

[0176] Take 3g of styrene-maleic anhydride linear copolymer (SMA, Mn = 45000g·mol -1 , MAH unit content is about 50%), 26g butanone (MEK), 1.89g 5-HMF, 0.06g DMAP in a 50mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 70°C for 24h. After the reaction, the reaction solution was poured into 200mL methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b1 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 25% and the aldehyde content of the polymer is 1.07 mmol·g -1 .

[0177] Take 1g of the prepared polymer P b1 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, styrene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c1 ).

[0178] Figure 1 The copolymer P c1 The actual photo shows that it is a light yellow powder.

[0179] Figure 2 and Figure 3 The polymer P b1 and copolymer P c1 Infrared spectrum of Figure 2 and Figure 3 It can be seen that the -1 The anhydride peak at 1680 cm-1 completely disappeared. -1 The aldehyde peaks at 1555 and 1660 cm -1 The amide peak at .

[0180] Example 2

[0181] Take 3g of styrene-maleic anhydride linear copolymer (SMA, Mn = 45000g·mol -1, MAH unit content is about 50%), 26g butanone, 1.89g 5-HMF, 0.06g DMAP in a 50mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 30°C for 72h. After the reaction, the reaction solution was poured into 200mL methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b2 ). According to H NMR analysis, the esterification rate was 16% based on the maleic anhydride unit, and the aldehyde content of the polymer was 0.72 mmol·g -1 .

[0182] Take 1g of the prepared polymer P b2 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, styrene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c2 ).

[0183] Example 3

[0184] Take 3g of styrene-maleic anhydride linear copolymer (SMA, Mn = 45000g·mol -1 , MAH unit content is about 50%), 26g butanone, 1.89g 5-HMF, 0.06g DMAP in a 50mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 120°C for 24h. After the reaction, the reaction solution was poured into 200mL methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b3 ). According to H NMR analysis, the esterification rate was 19% based on the maleic anhydride unit, and the aldehyde content of the polymer was 0.84 mmol·g -1 .

[0185] Take 1g of the prepared polymer P b3 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, styrene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c3 ).

[0186] Example 4

[0187] Take 3g of styrene-maleic anhydride linear copolymer (SMA, Mn = 45000g·mol-1 , MAH unit content is about 50%), 26g butanone, 1.89g 5-HMF in a 50mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 70°C for 24h. After the reaction, the reaction solution was poured into 200mL methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b4 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 9% and the aldehyde content is 0.42 mmol·g -1 .

[0188] Take 1g of the prepared polymer P b4 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, styrene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c4 ).

[0189] Example 5

[0190] Take 3g of styrene-maleic anhydride linear copolymer (SMA, Mn = 45000g·mol -1 , MAH unit content is about 50%), 26g butanone, 1.89g 5-HMF, 0.3g TEA in a 50mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 70°C for 24h. After the reaction, the reaction solution was poured into 200mL methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b5 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 28% and the aldehyde content is 1.18 mmol·g -1 .

[0191] Take 1g of the prepared polymer P b5 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, styrene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c5 ).

[0192] Example 6

[0193] Take 3g of styrene-maleic anhydride linear copolymer (SMA, Mn = 45000g·mol -1, MAH unit content is about 50%), 26g butanone, 0.189g 5-HMF, 0.06g TEA in a 50mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 70°C for 24h. After the reaction, the reaction solution was poured into 200mL methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b6 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 4% and the aldehyde content is 0.20 mmol·g -1 .

[0194] Take 1g of the prepared polymer P b6 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, styrene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c6 ).

[0195] Example 7

[0196] Take 3g of styrene-maleic anhydride linear copolymer (SMA, Mn = 45000g·mol -1 , MAH unit content is about 50%), 26g butanone, 5.67g 5-HMF, 0.06g TEA in a 50mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 70°C for 24h. After the reaction, the reaction solution was poured into 200mL methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b7 ). According to H NMR analysis, the esterification rate was 55% and the aldehyde content was 2.03 mmol·g based on the maleic anhydride unit. -1 .

[0197] Take 1g of the prepared polymer P b7 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, styrene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c7 ).

[0198] Figure 4 and Figure 5 The copolymer P b7 and copolymer P c7 The H NMR spectrum of Figure 4 and Figure 5 It can be seen that the peak of aldehyde hydrogen at 9.5 ppm is retained, and the peak of aromatic hydrogen on the benzene ring at 5.8-7.6 ppm remains unchanged.

[0199] Example 8

[0200] Take 1.5g of styrene-maleic anhydride linear copolymer (SMA, Mn = 45000g·mol -1 , MAH unit content is about 50%), 26g butanone, 1.89g 5-HMF, 0.06g TEA in a 50mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 70°C for 24h. After the reaction, the reaction solution was poured into 200mL methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b8 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 13% and the aldehyde content is 0.60 mmol·g -1 .

[0201] Take 1g of the prepared polymer P b8 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, styrene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c8 ).

[0202] Example 9

[0203] Take 6g of styrene-maleic anhydride linear copolymer (SMA, Mn = 45000g·mol -1 , MAH unit content is about 50%), 26g butanone, 5.67g 5-HMF, 0.06g TEA in a 50mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 70°C for 24h. After the reaction, the reaction solution was poured into 200mL methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b9 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 30% and the aldehyde content is 1.25 mmol·g -1 .

[0204] Take 1g of the prepared polymer P b9In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, styrene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c9 ).

[0205] Example 10

[0206] Take 2g of isobutylene-maleic anhydride linear copolymer (IB-MA, Mn = 6600g·mol -1 , MAH unit content is about 50%), 17g N,N-dimethylformamide, 1.26g 5-HMF, 0.04g DMAP in a 48mL single-necked flask, stirred for 0.5h, and a light yellow clear transparent solution was obtained. The reaction was carried out at 65°C for 24h. After the reaction, the reaction solution was poured into 200mL of methyl tert-butyl ether, and the polymer was precipitated. After centrifugation, washing, and dissolution and precipitation were repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, isobutylene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b10 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 10% and the aldehyde content is 0.46 mmol·g -1 .

[0207] Take 1g of the prepared polymer P b10 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, isobutylene and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c10 ).

[0208] Figure 6 The copolymer P b10 Actual photo of the product, which is a yellow liquid.

[0209] Embodiment 11

[0210] Take 2g of propylene-maleic anhydride linear copolymer (PP-MA), 17g of butanone, 1.26g of 5-HMF, and 0.04g of DMAP in a 48mL single-necked flask and stir for 0.5h to obtain a light yellow clear transparent solution. React at 65°C for 24h. After the reaction, pour the reaction solution into 200mL of methyl tert-butyl ether, and the polymer precipitates. After centrifugation, washing, and dissolution and precipitation are repeated three times, after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, propylene, and maleic acid mono(5-hydroxymethylfurfural) ester (PP-MA) can be obtained. b11 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 22% and the aldehyde content is 0.96 mmol·g -1 .

[0211] Take 1g of the prepared polymer P b11 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, propylene, and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c11 ).

[0212] Example 12

[0213] Take 2g of dephenolized phenol oil-maleic anhydride linear copolymer (DPPO-MA), 17g of butanone, 1.26g of 5-HMF, and 0.04g of DMAP in a 48mL single-necked flask and stir for 0.5h to obtain a light yellow clear transparent solution. React at 65°C for 24h. After the reaction, pour the reaction solution into 200mL of methyl tert-butyl ether, and the polymer precipitates. After centrifugation, washing, and dissolution and precipitation are repeated three times, after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, dephenolized phenol oil monomer, and maleic acid mono(5-hydroxymethylfurfural) ester (P b12 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 16% and the aldehyde content is 0.72 mmol·g -1 .

[0214] Take 1g of the prepared polymer P b12 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain an aldehyde-containing water-soluble terpolymer (P c12 ).

[0215] Example 13

[0216] Take 2g C5 fraction-styrene-maleic anhydride linear copolymer (C5-SMA), 17g butanone, 1.26g 5-HMF, 0.04g DMAP in a 48mL single-necked flask, stir for 0.5h, and obtain a light yellow clear transparent solution. React at 65°C for 24h. After the reaction, pour the reaction solution into 200mL methyl tert-butyl ether, and the polymer precipitates. After centrifugation, washing, and dissolution and precipitation are repeated three times, after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, C5 fraction monomer, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b13 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 20% and the aldehyde content is 0.88 mmol·g -1 .

[0217] Take 1g of the prepared polymer P b13In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain a water-soluble terpolymer containing aldehyde groups based on maleamic acid, C5 fraction monomer, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester structure (P c13 ).

[0218] Embodiment 14

[0219] Take 2g C9 fraction-styrene-maleic anhydride linear copolymer (C9-SMA), 17g butanone, 1.26g 5-HMF, 0.04g DMAP in a 48mL single-necked flask, stir for 0.5h, and obtain a light yellow clear transparent solution. React at 65°C for 24h. After the reaction, pour the reaction solution into 200mL methyl tert-butyl ether, and the polymer precipitates. After centrifugation, washing, dissolution and precipitation are repeated three times, and after drying, a pure aldehyde-containing terpolymer based on maleic anhydride, C9 fraction monomer, styrene, and maleic acid mono(5-hydroxymethylfurfural) ester (P b14 ). According to H NMR analysis, based on the maleic anhydride unit, the esterification rate is 20% and the aldehyde content is 0.88 mmol·g -1 .

[0220] Take 1g of the prepared polymer P b14 In a 100 mL beaker, high-purity ammonia was introduced for 10 min to obtain an aldehyde-containing water-soluble terpolymer (P c14 ).

[0221] The types of raw materials, amounts, reaction conditions, esterification rates and aldehyde content in Examples 1 to 14 are listed in Table 1 below.

[0222] Table 1

[0223]

[0224] Embodiment 15

[0225] Take 1 g of the polymer P prepared in Example 1 c1 In a 100 mL beaker, 10 mL of 1 M NaOH aqueous solution was added thereto, and the mixture was stirred at room temperature for 10 min for neutralization reaction to obtain an aldehyde-containing water-soluble terpolymer (P d1 ).

[0226] <Testing and Evaluation>

[0227] 1. Hydrophobicity evaluation

[0228] Take 1g of polymer P b7 and P c7 , respectively dissolved in 199g of distilled water to prepare a 0.5wt% aqueous solution. b7 and P c7 The polymer was immersed in an aqueous solution of about 5s, taken out and dried at room temperature, and heat-treated in an oven at 80°C for 30min to obtain a polymer P b7 and P c7 Xuan paper after sizing.

[0229] Contact angle test method: Place the treated rice paper on a glass slide and use an OCA200 contact angle meter (purchased from Dataphysics, Germany) to test the water contact angle. The injection volume for each test is 3 μL. After the water droplet is dropped on the paper surface, the syringe is raised and the video recording mode is used to start recording data within 300 seconds. The sampling rate is 1 Hz, that is, one sample per second.

[0230] Surprisingly, it was found that the polymer P after the introduction of furfural groups c7 Used in paper sizing, it can make the surface of paper hydrophobic after low temperature heat treatment. Figure 7 As shown, the aldehyde group introduced into P c7 After sizing, the water contact angle of Xuan paper decreased from 114° to 72° within 5 minutes and gradually stabilized, showing obvious hydrophobic and waterproof effects. b7 After sizing, Xuan paper absorbs water droplets into the paper in about 20 seconds, and has no hydrophobic effect. The heat treatment temperature of polymers containing amide acid structures reported in the literature is generally 120-160°C when used for paper sizing. Therefore, aldehyde-containing polymers are expected to be used in the field of paper sizing agents and achieve a significant reduction in heat treatment temperature.

[0231] Industrial Applicability

[0232] The polymer of the present invention can be widely used as an aldehyde substance in industry, for example, in organic synthesis, biomedicine, agriculture, textile industry, construction industry and other fields, especially as a paper sizing material or a wood adhesive.

Claims

1. A polymer, characterized in that Contains structural unit A, structural unit B and structural unit C, wherein The structural unit A is at least one selected from the structural units represented by the following formulae (1) to (4): In structures (3) and (4), M + Metal ions or ammonium ions The structural unit B is a structural unit derived from an olefin monomer; The structural unit C is at least one selected from the structural units represented by the following formula (5) and formula (6): In structure (6), M + Metal ions or ammonium ions 2. The polymer according to claim 1, characterized in that The olefin monomer is at least one selected from monoolefins or diolefins having 2 to 20 carbon atoms, styrene and its derivatives, and condensed-ring aromatic olefins; Preferably, the olefin monomer is at least one selected from ethylene, propylene, isobutylene, butadiene, isoprene, cyclopentadiene, dicyclopentadiene, styrene and its derivatives, indene, benzofuran, and benzothiophene; Preferably, the olefins are derived from at least one of the following raw materials: C4 fraction, C5 fraction, C8 fraction, C9 fraction, ethylene tar, crude gasoline, C4 and above byproduct fractions of coal-to-olefins, coal tar, and coal-to-liquids. The C4 fraction is preferably selected from refining C4 and naphtha cracking C4, and the crude gasoline is preferably selected from pre-ether gasoline, catalytic cracking gasoline, catalytic hydrogenation gasoline, and coking gasoline.

3. The polymer according to claim 1, characterized in that Based on the total molar number of the structural units of the polymer, the content of the structural unit A is 5 to 45 mol%, the content of the structural unit B is 30 to 70 mol%, and the content of the structural unit C is 1 to 35 mol%; Preferably, based on the total molar number of the structural unit A and the structural unit C, the content of the structural unit C is 1 to 50 mol %, preferably 10 to 45 mol %.

4. The polymer according to claim 1, characterized in that Aldehyde content: 0.05~3mmol·g -1 .

5. The method for preparing a polymer according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) reacting a precursor polymer with 5-hydroxymethylfurfural, wherein the precursor polymer comprises a structural unit A represented by formula (1) and a structural unit B derived from an olefin monomer; (2) Optionally, subjecting the polymer obtained in step (1) to aminolysis and / or neutralization reaction.

6. The preparation method according to claim 5, characterized in that: In step (1), an acid anhydride group in the structural unit represented by formula (1) is subjected to an esterification reaction with a hydroxyl group in 5-hydroxymethylfurfural in the presence of a catalyst; the catalyst is preferably an acid or a base, and the base is preferably one or more selected from pyridine, 4-dimethylaminopyridine, triethylamine, and 1,5,7-triazabicyclo[4.4.0]dec-5-ene; the acid is preferably one or more selected from acetic acid, propionic acid, n-butyric acid, succinic acid, p-toluenesulfonic acid, hydrochloric acid, and sulfuric acid; In step (1), the molar ratio of 5-hydroxymethylfurfural to the structural unit represented by formula (1) is (0.1-3):1, preferably (1-2):1; In step (2), the polymer obtained in step (1) is contacted with ammonia gas to perform the aminolysis reaction and / or the polymer obtained in step (1) is contacted with a metal hydroxide or a metal carbonate to perform the neutralization reaction.

7. The preparation method according to claim 5, characterized in that: In step (1), the precursor polymer is dispersed or dissolved in a solvent, and then 5-hydroxymethylfurfural is added thereto to react the precursor polymer with 5-hydroxymethylfurfural; Preferably, the solvent is one or more selected from ketone solvents, ester solvents, ether solvents, amide solvents, and sulfoxide solvents.

8. The preparation method according to claim 6, characterized in that: The temperature of the esterification reaction in step (1) is 40 to 150° C., and the time of the esterification reaction is 0.1 to 100 hours; the time of the aminolysis reaction in step (2) is 0.1 to 30 minutes, preferably 1 to 10 minutes; the time of the neutralization reaction in step (2) is 0.1 to 30 minutes, preferably 1 to 10 minutes.

9. The preparation method according to claim 5, characterized in that: The following steps are also included: (1') subjecting the electron accepting monomer and the olefin monomer to self-stabilizing precipitation polymerization to obtain the precursor polymer; Wherein, the electron accepting monomer is maleic anhydride; Preferably, at least one selected from the group consisting of C4 fraction, C5 fraction, C8 fraction, C9 fraction, ethylene tar, crude gasoline, C4 and above byproduct fractions of coal-to-olefins, coal tar, and coal-to-liquid is used as the raw material of the olefin monomer; The C4 fraction is preferably selected from refining C4 and naphtha cracking C4; the crude gasoline is preferably selected from pre-ether gasoline, catalytic cracking gasoline, catalytic hydrogenation gasoline and coking gasoline.

10. Use of the polymer according to any one of claims 1 to 4 as a paper sizing agent or a wood adhesive.

Citation Information

Patent Citations

  • Preparing method for bionic adhesive coatings comprising aldehyde and amino phosphorylcholine polymers

    CN108715644A

  • Preparation method of poly-aldehyde polymer tanning agent

    CN110041451A

  • Treatment method of C5 fraction and application of olefinic bond-containing compound

    CN113563152A

  • Self-stabilization precipitation polymerization method using ether-containing solvent

    CN115926024A

  • Functional copolymer and preparation method thereof

    CN117417481A